Inhibition of HDAC6 Activity Protects Against Endothelial Dysfunction and Atherogenesis in vivo: A Role for HDAC6 Neddylation - Nomura, Yohei; Nakano, Mitsunori; Woo Sung, Hyun; Han, Mingming; Pandey, Deepesh (Frontiers in Physiology, 2021)
We previously reported that histone deacetylase 6 (HDAC6) has an important role in endothelial cell (EC) function in vitro. However, whether HDAC6 plays a role in atherogenesis in vivo and the mechanism(s) that control HDAC6 activity/expression in response to atherogenic stimuli are unclear. The goals of this study were to determine whether HDAC6 inhibitor tubacin attenuates atherogenesis and to elucidate specific molecular mechanism(s) that regulate endothelial HDAC6 expression/activity. We evaluated whether administration of tubacin attenuated or reversed the endothelial dysfunction and atherosclerosis induced in mice by a single intraperitoneal injection of adeno-associated viruses encoding liver-target PCSK9 gain-of-function mutant followed by a high fat diet (HFD) for 18 weeks. Tubacin significantly blunted PCSK9-induced increases in pulse wave velocity (index of vascular stiffness and overall vascular health) that are also seen in atherogenic mice. Furthermore, tubacin protected vessels from defective vasorelaxation, as evaluated by acetylcholine-mediated relaxation using wire myograph. Plaque burden defined by Oil Red O staining was also found to be significantly less in mice that received tubacin than in those that received PCSK9 alone. Inhibition of the NEDDylation pathway with MLN4924, an inhibitor of NEDD8-activating enzyme 1 (NAE1), significantly increased HDAC6 activity in HAECs. Interestingly, HDAC6 expression remained unchanged. Further, HAECs exposed to the atherogenic stimulus oxidized low-density lipoprotein (OxLDL) exhibited enhanced HDAC6 activity, which was attenuated by pretreatment with MLN4924. The HDAC6 NEDDylation molecular pathway might regulate genes related to endothelial control of vasomotor tone, reactivity, and atherosclerosis. Tubacin may represent a novel pharmacologic intervention for atherogenesis and other vasculopathies.